The Impact of Financial Distress and Company Size on Accounting Conservatism - Tuharea, Firdaus Indrajaya; Fatimah, Nur (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The study aims to explore and illustrate the relationship between accounting conservatism financial hardship and business size for companies in the property and real estate sectors listed on the IDX between 2018 and 2020. Accounting conservatism is the dependent variable in this study. A recording method known as accounting conservatism anticipates all losses as opposed to simply gains. Earnings are not recognized unless they are legally verified and show that real money will be received. Financial distress is the initial independent variable that represents the phase of a company’s financial deterioration that takes place before bankruptcy or liquidation. The second independent variable is firm size, which is a scale that allows the company’s size to be categorized according to a number of factors, such as market capitalization, net sales, and total assets. This study employed a quantitative methodology, with statistical data analysis performed using SPSS Version 21. The procedure employed the multiple linear regression analysis method, which included the use of the coefficient of determination, a traditional assumption text, and hypothesis testing. The findings show that 1) Firm Size and Financial Distress have a somewhat substantial impact on Accounting Conservatism. 2) Accounting conservatism is significantly impacted by both firm size and financial distress at the same time.